PENDEKATAN SISTEM PADA SISTEM EKONOMI DAN KOPERASI MEMASUKI ABAD 21 - P.C. Suroso (Bina Ekonomi, 1999)
Cooperative emerged as a reaction to unfairness condition caused by capitalism. As an Economic institution Cooperative had a specific vision on social justice that has been spelled In basic principles: democracy, justice and volunteering. Those basic principles were bound By fundamental ethics namely honesty, caring and diversity. As a result, Cooperative has Become a human culture movement to achieve  an integrated and safe society. However, the Implementation of Cooperative at the moment is far from its values and principles. This  paper Will discuss the emerging of Cooperative, the basic principles and values of Cooperative and Its implementation and finally the existence of Cooperative in 21st century.